Design and Synthesis of Metal Complexes of (2E)-2-[(2E)-3-Phenylprop-2-en-1-ylidene]hydrazinecarbothioamide and Their Photocatalytic Degradation of Methylene Blue. (2nd December 2013) - Krishna, P. Murali; Reddy, N. B. Gopal; Kottam, Nagaraju; Yallur, B. C.; Katreddi, Hussain Reddy
Abstract : The photocatalytic degradation has been considered to be an efficient process for the degradation of organic pollutants, which are present in the effluents released by industries. The photocatalytic bleaching of cationic dye methylene blue was carried out spectrometrically on irradiation of UV light using Cu(II), Ni(II), and Co(II) complexes of (2 E )-2-[(2 E )-3-phenylprop-2-en-1-ylidene]hydrazinecarbothioamide (HL). The effects of pH and metal ion were studied on the efficiency of the reaction. Cu(II) complex shows better catalytic activity and the highest percentage degradation (~ 88.8%) of methylene blue was observed at pH 12. A tentative mechanism has also been proposed for the photocatalytic degradation of methylene blue.